2011
DOI: 10.3109/09593985.2011.578706
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the use of outcome measures in physical therapy practice

Abstract: Use of outcome measures in physical therapy practice is central to evaluating the effectiveness of treatment interventions, providing accountability and addressing quality of physical therapy programs. There is limited discussion on barriers and facilitators to using outcome measures in physical therapy practice. The purpose of this study was to identify factors that influence a physical therapist when deciding to use outcome measures in clinical practice. Participants were 21 physical therapists, seven each f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 23 publications
0
60
1
1
Order By: Relevance
“…35 Preliminary research into the perceived benefits and barriers of outcomes assessment has provided insight into how the theory of planned behavior can be used to explain clinician behaviors. Previous research 14,16,33,36 has confirmed that a positive attitude toward the value of outcomes assessment plays a large role for those health care professionals who choose to measure outcomes systematically. Changes in policies and job site culture may affect social norms and increase willingness to use standardized outcomes measures.…”
Section: Overall Perceptions Of Promsmentioning
confidence: 97%
See 1 more Smart Citation
“…35 Preliminary research into the perceived benefits and barriers of outcomes assessment has provided insight into how the theory of planned behavior can be used to explain clinician behaviors. Previous research 14,16,33,36 has confirmed that a positive attitude toward the value of outcomes assessment plays a large role for those health care professionals who choose to measure outcomes systematically. Changes in policies and job site culture may affect social norms and increase willingness to use standardized outcomes measures.…”
Section: Overall Perceptions Of Promsmentioning
confidence: 97%
“…Changes in policies and job site culture may affect social norms and increase willingness to use standardized outcomes measures. 29,36 Constraints in practice settings (perceived behavioral control), such as time and access to support, also affect a clinician's decision to use standardized measures. 26 Moreover, clinicians may not use PROMs because they do not believe the available instruments meet their clinical needs.…”
Section: Overall Perceptions Of Promsmentioning
confidence: 99%
“…Nonetheless, rehabilitation therapists do not routinely use validated assessment or outcome measures, despite encouragement to incorporate them into routine practice [10]. Frequently cited barriers to clinical use of outcome measures include time constraints, lack of equipment, institution culture and unfamiliarity with assessment tools and their benefits [1,11]. Furthermore, the large number of validated tools hinders consistency of practice even within a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…1 One barrier that restricts the use of OMs is lack of knowledge to choose the most appropriate OM for a given patient or situation. 2,3 Selection of OMs has received considerable attention, [4][5][6][7][8][9][10] but little information exists to specifically describe clinical decision-making processes that clinicians can use in practice. Rehabilitation therapists working with people with multiple sclerosis (MS) have additional challenges in OM selection because of the heterogeneous patient population and symptom variability in individual patients.…”
mentioning
confidence: 99%